Konsep Media Pembelajaran Menyimak di Kelas Tinggi - Bintang Mahrani Abdullah; Miftahul Jannah; Yunita Azhari; Juni Sahla Nasution (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
Listening learning media in higher classes is an intermediary tool that makes it easier for students to focus on understanding learning material. This research aims to determine the concept of listening learning media in high school. This research method uses qualitative methods based on literature study. Literature study is a method that collects various sources to be used as references. The results of this research show that there are still many students who are less serious about understanding the learning material. Therefore, listening learning media is very important to use in the learning process. Because, using listening learning media can make it easier for students to focus on understanding the meaning of the learning they are listening to and can make learning more interesting and not boring.